Micronodular pattern of organizing pneumonia: Case report and systematic literature review. Issue 3 (January 2017) - Lebargy, François; Picard, Davy; Hagenburg, Jean; Toubas, Olivier; Perotin, Jeanne-Marie; Sandu, Sebastian; Deslee, Gaëtan; Dury, Sandra
Abstract: Rationale: Organizing pneumonia (OP) is a clinicopathological entity characterized by granulation tissue plugs in the lumen of small airways, alveolar ducts, and alveoli. OP can be cryptogenic (primary) (COP) or secondary to various lung injuries. Patient concerns: We report the case of a 38-year-old male smoker with COP presenting in the form of diffuse micronodules on computed tomography (CT) scan and describe the clinical, radiological, and functional characteristics of micronodular pattern of organizing pneumonia (MNOP) based on a review of the literature including 14 cases. Patients were younger (36.3 ± 15.5 years) than those with the classical form of OP. The clinical presentation was subacute in all cases with a mean duration of symptoms before admission of 14.5 ± 13.2 days. The radiological pattern was characterized by centrilobular nodules and "bud-in-tree" sign in 86.7% of patients. The diagnosis was based on histological examination of transbronchial (28.6%) or surgical biopsies (71.4%). Diagnosis: An associated condition was identified in 65% of cases and included illicit substance abuse (44.5%), myeloproliferative disease (33.5%), and infections (22%). Outcomes: Steroid therapy was effective in all patients with improvement of symptoms and documented radiologic resolution. No relapse was recorded. Lessons: MNOP should be recognized and distinguished from other diagnoses, mainly infectious bronchiolitis and disseminated tumor, as it requires early specific steroid therapy.